Implementasi Kurikulum 2013 di MTs Yaqin 1 Kwang Rundun Kecamatan Jerowaru ( Masalah dan Solusinya ) - Sirajun Nasihin (PALAPA, 2016)
This study aims to find out what are the problems faced by the MTs Yaqin 1 Kwang Rundun in efforts Implementation of Curriculum 2013 and solutions are developed to solve the problem. To collect research data, the authors used three data collection techniques namely; observation, interviews, and documentation. Researchers directly to the location of the study where the author is an integral part of the foundation of this education provider so you can easily get access to inside information. From this research, the authors came to the conclusion that the problems encountered in the implementation of the curriculum in 2013 at MTs Yaqin 1 Kwang Rundun is, among others; the limited information on the curriculum system in 2013, the lack of learning facilities became vital elements which books the students, there are no available infrastructure for the primary learning support such implementation; laboratory, teaching aids, instructional media and professional competence of teachers has not been adequate ". While the solution the solution is to build cooperation with parents, school committee and stake holders as part of the management of public relations of the school to inform the public that the schools have a vital need that has not been reached, the teachers have a strong willingness to learn so sought oftimalisasi MGMPs, and headmaster has a strong determination to move forward so that it can set aside a budget for the procurement needs.